Discovery of Potential Candidate Genes for Coat Colour in Wuzhishan Pigs by Integrating SNPs and mRNA Expression Analysis - Qiao Xu; Yabiao Luo; Zhe Chao; Jibin Zhang; Xiaolei Liu; Danqin Tu; Qin Guo; Ruiping Sun; Feng Wang; Meiying Fang (Animals)
Despite identifying genes regulating the coat colour in Western pig breeds, the genetic basis of the coat colour in Chinese indigenous pigs is still not understood due to the diversity of indigenous breeds and their genetic differences from exotic pigs. In this study, 215 Wuzhishan pigs with three coat colour patterns (white, black, and black-back/white-belly) were used to conduct a genome-wide association analysis. We found that genes responsible for the coat colour in the Wuzhishan breed are located on chromosome 8. Ninety-seven genome-wide significant SNPs are related to the animal’s coat colour. Using a haplotype-sharing analysis, we narrowed the potential candidate region to a 10.1 Mb interval encompassing only one gene, RAPGEF2, which participates in the regulation of melanogenesis. Two additional candidate genes, PDGFRA and KIT, are located within 1 Mb of the genome-wide significant SNPs. Gene ontology analysis and literature mining suggest that these candidate genes are associated with the animal’s coat colour. mRNA expression results revealed that RAPGEF2 and PDGFRA had significantly higher expressions in black pigs than in white pigs and higher expressions in black skin than in white skin from the same black-back/white-belly pigs. These results suggest that RAPGEF2 and PDGFRA are potential candidate genes regulating the coat colour in Wuzhishan pigs. Interestingly, mutations of KIT (a gene duplication and a G to A substitution at the splicing site in intron 17) were detected in white Wuzhishan pigs but not in black-back/white-belly or black pigs, suggesting a close genetic relationship between white Wuzhishan pigs and Western white pig breeds. In summary, these results indicate that the expression of RAPGEF2 and PDGFRA may cause the coat colour variation by influencing the deposition of melanin, while the mutation of KIT causes the white coat colour. Our results may provide a theoretical basis for the breeding of white coat colour Wuzhishan pigs, and shed light on the complex genetic background of coat colour variations in indigenous Chinese pig breeds.